PENGARUH KUALITAS PRODUK, HARGA DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUNSCREEN AZARINE DI PLATFORM SHOPEE STUDI KASUS KECAMATAN SUMBAWA - Raizah Risky Utami; Tomy Dwi Cahyono (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the influence of product quality, price, and social media on purchasing decisions for Azarine sunscreen products on the Shopee platform, focusing on consumers in Sumbawa District. The background of the study is based on the increasing use of e-commerce and public awareness of the importance of skin protection, which drives the growth in demand for skincare products, especially sunscreen. The method used is quantitative descriptive with data collection techniques through questionnaires to 100 respondents. Data were analyzed using multiple linear regression to test the influence of independent variables on purchasing decisions. The results of the study indicate that the three variables—product quality, price, and social media—have a positive and significant effect on purchasing decisions. These findings indicate that consumers in Sumbawa District tend to consider aspects of quality, affordability, and the influence of social media in choosing Azarine sunscreen products on the Shopee platform. This study is expected to contribute to business actors and academics in understanding consumer behavior in the digital era, especially in sub- district